W poszukiwaniu uniwersalnej metody upraszczania pism urzędowych i decyzji administracyjnych - Piekot, Tomasz (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
Since 2018, the key Polish offices have been signing the declaration for plain language, one of the key provisions of which is the call for the simplification of official documents sent to citizens. The aim of the article is to present the methods for simplifying texts, created at the University of Wrocław. The author focuses in particular on indicating the limitations of the proposed method in reference to administrative (fiscal) decisions and those decisions which are not documents from the legal perspective. The article presents examples of simplified documents and decisions.